Regenerated polyester textile fabric and preparation process thereof
By combining the modified nano-silver-carried zirconium phosphate with flame retardant, and melt blending and spinning with regenerated polyester, a regenerated polyester textile fabric with excellent flame retardant and antibacterial properties was prepared, which solved the combustion of RPET fibers and health and safety issues.
Patent Information
- Application Number
- CN202411554866.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing regenerated polyethylene terephthalate (RPET) fibers have great flammability during combustion, which may cause the fire to spread and may breed bacteria after long-term use, affecting the hygiene and safety of the product.
Under nitrogen protection, the modified nano-silver-carried zirconium phosphate reacts with a flame retardant in xylene to form a composite, and melt blends with regenerated polyester slices, extrudes and granulates, and then melt-spinning and rolling The modified polyester fiber is prepared by winding and stretching, and finally woven into a recycled polyester textile fabric.
The flame retardant properties and antibacterial properties of textile fabrics are significantly improved, the amount of flame retardant and antibacterial agent is added is reduced, and the spinability of recycled polyester and the physical and mechanical properties of the fibers are guaranteed.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile fabrics, in particular to a regenerated polyester textile fabric and a preparation process thereof. Background Art
[0002] Recycled polyethylene terephthalate (RPET) fiber products have attracted widespread attention due to their excellent environmental characteristics. RPET is made by recycling and reprocessing polyethylene terephthalate (PET), a process that not only reduces the impact of plastic waste on the environment, but also reduces the energy consumption of producing new materials. RPET fiber has excellent strength, can withstand large tensile forces, and exhibits good shrinkage resistance during use, which makes it have great advantages in textile applications.
[0003] However, RPET still has a big shortcoming in terms of flammability. During the combustion process, serious molten droplets will occur, which not only increases the risk of fire, but also releases a large amount of heat, which may cause the fire to spread. In addition, after long-term use, RPET may breed bacteria due to its surface characteristics, thus affecting the sanitation and safety of the product. These factors have, to a certain extent, limited the application of RPET in certain areas with high safety or high sanitation requirements.
[0004] Therefore, we propose a recycled polyester textile fabric and a preparation process thereof. Summary of the invention
[0005] The purpose of the present invention is to provide a regenerated polyester textile fabric and a preparation process thereof to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A preparation process of a regenerated polyester textile fabric comprises the following steps:
[0008] Step S1: Under nitrogen protection, ultrasonically disperse the modified nano silver-loaded zirconium phosphate in xylene, heat to 75-85° C., add benzoyl peroxide and flame retardant and mix evenly, react for 8-10 hours, cool to room temperature, centrifuge, wash and dry to obtain a composite;
[0009] Step S2: mixing the dried recycled polyester chips and the composite, adding them into a twin-screw extruder, melt blending, extruding and granulating, and obtaining a modified polyester masterbatch;
[0010] Step S3: mixing the modified polyester masterbatch and the recycled polyester chips, performing melt spinning, winding and stretching treatment to obtain modified polyester fibers; and plying, twisting and weaving the modified polyester fibers to obtain recycled polyester textile fabrics.
[0011] Furthermore, the composite comprises the following components by mass: 1-3 parts of modified nano silver-loaded zirconium phosphate, 2-10 parts of flame retardant, 0.1-0.3 parts of benzoyl peroxide, and 50-150 parts of xylene.
[0012] Furthermore, the preparation method of the modified nano silver-loaded zirconium phosphate is as follows:
[0013] The nano silver-loaded zirconium phosphate was ultrasonically dispersed in deionized water, glacial acetic acid was added to adjust the pH value of the system to 4-5, and then a mixed solution of γ-methacryloxypropyltrimethoxysilane and cyclohexane was added dropwise for 1-2 hours, the temperature was raised to 50-60°C, the reaction was carried out for 3-5 hours, and the modified nano silver-loaded zirconium phosphate was obtained after filtering, washing and drying.
[0014] Furthermore, the mass ratio of the nano silver-loaded zirconium phosphate, deionized water, γ-methacryloxypropyltrimethoxysilane and cyclohexane is 1:(40-50):(1-2):(20-40).
[0015] Furthermore, the preparation method of the flame retardant is as follows:
[0016] Step (1): under nitrogen protection, eugenol and epichlorohydrin are mixed evenly, benzyltriethylammonium chloride is added, reacted at 90-100° C. for 4-6 hours, cooled to 50-60° C., sodium hydroxide solution is added, and the reaction is continued for 3-5 hours. After filtering, washing, and rotary evaporation, eugenol glycidyl ether is obtained;
[0017] Step (2): Under nitrogen protection, DOPO and eugenol glycidyl ether are mixed evenly, the temperature is raised to 130-140° C., triphenylphosphine is added, the reaction is carried out for 5-7 hours, and the mixture is cooled to room temperature to obtain modified DOPO;
[0018] Step (3): under nitrogen protection, heat cyanuric chloride to 70-80° C., add modified DOPO and calcium chloride, react for 30-50 min, raise the temperature to 90-100° C., continue to react for 2-4 h, filter, wash and dry to obtain a dichloro compound;
[0019] Step (4): mixing boric acid, diethanolamine and toluene uniformly, and reacting under reflux at 115-125° C. until no more water is produced in the system, and distilling under reduced pressure, washing and drying to obtain diethanolamine borate;
[0020] Step (5): uniformly mix the dichloro compound, diethanolamine borate and DMF, react at 120-130° C. for 1-2 h, evaporate the DMF under reduced pressure, raise the temperature to 190-200° C. for 2-4 h, and obtain a flame retardant after washing and drying.
[0021] Furthermore, in the step (1), the mass ratio of eugenol to epichlorohydrin, benzyltriethylammonium chloride and sodium hydroxide solution is 1:(1.7-1.8):(0.02-0.03):(1.6-1.7).
[0022] Furthermore, in step (1), the concentration of the sodium hydroxide solution is 30 wt %.
[0023] Furthermore, in the step (2), the mass ratio of DOPO, eugenol glycidyl ether and triphenylphosphine is 1:(1.0-1.5):(0.03-0.05).
[0024] Furthermore, in the step (3), the mass ratio of cyanuric chloride, modified DOPO and calcium chloride is 1:(2-3):(0.01-0.03).
[0025] Furthermore, in the step (4), the mass ratio of boric acid, diethanolamine and toluene is 1:(3.5-4.0):(4-6).
[0026] Furthermore, in the step (5), the mass ratio of the dichloro compound, diethanolamine borate and DMF is 1:(0.4-0.5):(2-3).
[0027] In the above technical scheme, biomass eugenol and epichlorohydrin are used as raw materials to synthesize eugenol glycidyl ether; a ring-opening reaction occurs between the PH bond of DOPO and the epoxy group of eugenol glycidyl ether to form a hydroxyl group, thereby obtaining a modified DOPO; then, by controlling the ratio of cyanuric chloride to the modified DOPO, a -Cl in cyanuric chloride reacts with the hydroxyl group on the modified DOPO to obtain a dichloro compound; finally, a condensation reaction occurs between the dichloro compound and diethanolamine borate to obtain a flame retardant containing N, P, and B, while also containing a carbon-carbon double bond.
[0028] Furthermore, in step S2, the mass ratio of the recycled polyester chips to the composite is 1:(0.05-0.20).
[0029] Furthermore, in step S3, the mass ratio of the modified polyester masterbatch to the recycled polyester chips is 1:(10-12).
[0030] Furthermore, the temperature of the melt blending is 230-270°C.
[0031] Furthermore, the melt spinning temperature is 270-290° C., and the winding speed is 600-900 m / min.
[0032] Furthermore, the process conditions of the stretching treatment are: the stretching multiple is 3-5 times, and the stretching rate is 700-900m / min.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. A regenerated polyester textile fabric and its preparation process of the present invention, eugenol is a natural ingredient with excellent antibacterial and calming effects, which is greener, more environmentally friendly and safer than other antibacterial ingredients, and eugenol glycidyl ether is synthesized by using biomass eugenol and epichlorohydrin as raw materials;
[0035] Under the action of triphenylphosphine catalyst, the epoxy group in eugenol glycidyl ether reacts with the PH bond in DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) to undergo a ring-opening reaction to generate hydroxyl groups to obtain modified DOPO; then, by controlling the slight excess of cyanuric chloride, one -Cl in cyanuric chloride reacts with the hydroxyl group on the modified DOPO to obtain a dichloro compound; finally, the dichloro compound undergoes a condensation reaction with diethanolamine borate to obtain a flame retardant containing N, P, and B, which also contains carbon-carbon double bonds, which not only enhances the flame retardant properties of textile fabrics, but also improves their antibacterial properties.
[0036] 2. A regenerated polyester textile fabric and its preparation process of the present invention are mainly flame retardants, and inorganic nano silver zirconium phosphate (AgZrP) is added for synergistic flame retardancy and antibacterial modification. AgZrP is a type of nano silver inorganic metal antibacterial agent, and the nanoparticles have a small particle size and a large relative surface area, which makes it very easy to agglomerate during the composite process; the nano silver zirconium phosphate is surface modified by γ-methacryloxypropyltrimethoxysilane coupling agent (MPS), and double bonds are introduced to obtain modified nano silver zirconium phosphate, which significantly improves its dispersibility in the polyester matrix and reduces the agglomeration phenomenon, thereby improving the mechanical properties of the fiber; then, under the action of an initiator, the modified nano silver zirconium phosphate reacts with the double bonds in the flame retardant to form a composite; the inorganic nanoparticle AgZrP combines synergistic flame retardancy and antibacterial properties, reduces the amount of flame retardants and antibacterial agents added, ensures the spinnability of the recycled polyester and the physical and mechanical properties of the fiber, and successfully prepares a regenerated polyester textile fabric with flame retardant and antibacterial properties. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] In this embodiment, the recycled polyester chips: brand RPET 110, sourced from Dongguan Aohua Plastic Trading Co., Ltd.; nano silver-loaded zirconium phosphate: silver content 3%, particle size 50-100nm, model YC-LSG200, sourced from Shanghai Yingcheng New Materials Co., Ltd.
[0039] In the following examples and comparative examples, 1 part is equal to 10 g.
[0040] Embodiment 1: A process for preparing a recycled polyester textile fabric, comprising the following processes:
[0041] Step S1: Under nitrogen protection, ultrasonically disperse 1 part of modified nano silver-loaded zirconium phosphate in 50 parts of xylene, heat to 75° C., add 0.1 part of benzoyl peroxide and 2 parts of flame retardant, mix well, react for 8 hours, cool to room temperature, centrifuge, wash, and dry to obtain a composite;
[0042] Step S2: 60 parts of the dried recycled polyester chips and 3 parts of the compound are mixed, added into a twin-screw extruder, melt-blended at 230° C., extruded and granulated to obtain a modified polyester masterbatch;
[0043] Step S3: 60 parts of modified polyester masterbatch and 600 parts of recycled polyester chips are mixed, and melt-spinning (temperature is 270° C.), winding (speed is 600 m / min) and stretching treatment (stretching multiple is 3 times, stretching speed is 700 m / min) are performed to obtain modified polyester fiber; the modified polyester fiber is ply-twisted and woven to obtain recycled polyester textile fabric;
[0044] The preparation method of modified nano silver-loaded zirconium phosphate is as follows:
[0045] Ultrasonic dispersion of 1 part of nano silver-loaded zirconium phosphate in 40 parts of deionized water, adding glacial acetic acid to adjust the system pH to 4, then dripping a mixed solution of 1 part of γ-methacryloxypropyltrimethoxysilane and 20 parts of cyclohexane, dripping for 1 hour, heating to 50°C, reacting for 3 hours, filtering, washing and drying to obtain modified nano silver-loaded zirconium phosphate;
[0046] The preparation method of the flame retardant is as follows:
[0047] Step (1): under nitrogen protection, 3 parts of eugenol and 5.1 parts of epichlorohydrin are mixed evenly, 0.06 parts of benzyltriethylammonium chloride are added, the mixture is reacted at 90° C. for 4 hours, the temperature is lowered to 50° C., 4.8 parts of 30 wt % sodium hydroxide solution are added, the mixture is reacted for 3 hours, and after filtering, washing and rotary evaporation, eugenol glycidyl ether is obtained;
[0048] Step (2): Under nitrogen protection, 3 parts of DOPO and 3 parts of eugenol glycidyl ether were mixed evenly, heated to 130° C., 0.09 parts of triphenylphosphine were added, reacted for 5 hours, and cooled to room temperature to obtain modified DOPO;
[0049] Step (3): Under nitrogen protection, heat 1.5 parts of cyanuric chloride to 70° C., add 3 parts of modified DOPO and 0.015 calcium chloride, react for 30 minutes, heat to 90° C., continue to react for 2 hours, filter, wash and dry to obtain a dichloro compound;
[0050] Step (4): 1 part of boric acid, 3.5 parts of diethanolamine and 4 parts of toluene are uniformly mixed, and refluxed at 115° C. until no water is produced in the system, and then distilled under reduced pressure, washed and dried to obtain diethanolamine borate;
[0051] Step (5): 3 parts of a dichloro compound, 1.2 parts of diethanolamine borate and 6 parts of DMF are mixed evenly, reacted at 120° C. for 1 hour, DMF is evaporated under reduced pressure, the temperature is raised to 190° C. for 2 hours, and a flame retardant is obtained after washing and drying.
[0052] Embodiment 2: A process for preparing a recycled polyester textile fabric, comprising the following processes:
[0053] Step S1: Under nitrogen protection, 2 parts of modified nano silver-loaded zirconium phosphate are ultrasonically dispersed in 100 parts of xylene, the temperature is raised to 80° C., 0.2 parts of benzoyl peroxide and 6 parts of flame retardant are added and mixed evenly, reacted for 9 hours, cooled to room temperature, centrifuged, washed, and dried to obtain a composite;
[0054] Step S2: 80 parts of the dried recycled polyester chips and 8 parts of the composite are mixed, added into a twin-screw extruder, melt-blended at 250° C., extruded and granulated to obtain a modified polyester masterbatch;
[0055] Step S3: 80 parts of modified polyester masterbatch and 880 parts of recycled polyester chips are mixed, and melt-spinning (temperature is 280° C.), winding (speed is 800 m / min) and stretching treatment (stretching multiple is 4 times, stretching speed is 800 m / min) are carried out to obtain modified polyester fiber; the modified polyester fiber is ply-twisted and woven to obtain recycled polyester textile fabric;
[0056] The preparation method of modified nano silver-loaded zirconium phosphate is as follows:
[0057] 2 parts of nano silver-loaded zirconium phosphate were ultrasonically dispersed in 90 parts of deionized water, glacial acetic acid was added to adjust the system pH to 4.5, and then a mixed solution of 3 parts of γ-methacryloxypropyltrimethoxysilane and 100 parts of cyclohexane was added dropwise for 1.5 hours, and the mixture was heated to 55°C and reacted for 4 hours. After filtering, washing and drying, the modified nano silver-loaded zirconium phosphate was obtained.
[0058] The preparation method of the flame retardant is as follows:
[0059] Step (1): Under nitrogen protection, 7 parts of eugenol and 12 parts of epichlorohydrin are uniformly mixed, 0.17 parts of benzyltriethylammonium chloride are added, the mixture is reacted at 95° C. for 5 hours, the temperature is lowered to 55° C., 11.5 parts of 30 wt % sodium hydroxide solution are added, the reaction is continued for 4 hours, and after filtering, washing, and rotary evaporation, eugenol glycidyl ether is obtained;
[0060] Step (2): Under nitrogen protection, 6 parts of DOPO and 7.2 parts of eugenol glycidyl ether were mixed evenly, the temperature was raised to 135° C., 0.24 parts of triphenylphosphine were added, the reaction was carried out for 6 hours, and the mixture was cooled to room temperature to obtain modified DOPO;
[0061] Step (3): Under nitrogen protection, heat 2.4 parts of cyanuric chloride to 75° C., add 6 parts of modified DOPO and 0.05 parts of calcium chloride, react for 40 minutes, heat to 95° C., continue to react for 3 hours, and obtain a dichloro compound by vacuum distillation;
[0062] Step (4): 2 parts of boric acid, 7.6 parts of diethanolamine and 10 parts of toluene are mixed uniformly, and refluxed at 120° C. until no water is produced in the system, and then distilled under reduced pressure, washed and dried to obtain diethanolamine borate;
[0063] Step (5): 6 parts of a dichloro compound, 2.7 parts of diethanolamine borate and 15 parts of DMF are mixed evenly, reacted at 125° C. for 1.5 hours, DMF is evaporated under reduced pressure, the temperature is raised to 195° C., reacted for 3 hours, and a flame retardant is obtained after washing and drying.
[0064] Embodiment 3: A process for preparing a recycled polyester textile fabric, comprising the following processes:
[0065] Step S1: Under nitrogen protection, 3 parts of modified nano silver-loaded zirconium phosphate are ultrasonically dispersed in 150 parts of xylene, the temperature is raised to 85° C., 0.3 parts of benzoyl peroxide and 10 parts of flame retardant are added and mixed evenly, reacted for 10 hours, cooled to room temperature, centrifuged, washed, and dried to obtain a composite;
[0066] Step S2: 65 parts of the dried recycled polyester chips and 13 parts of the compound are mixed, added into a twin-screw extruder, melt-blended at 270° C., extruded and granulated to obtain a modified polyester masterbatch;
[0067] Step S3: 65 parts of modified polyester masterbatch and 780 parts of recycled polyester chips are mixed, and melt-spinning (temperature is 290° C.), winding (speed is 900 m / min) and stretching treatment (stretching multiple is 5 times, stretching speed is 900 m / min) are carried out to obtain modified polyester fiber; the modified polyester fiber is ply-twisted and woven to obtain recycled polyester textile fabric;
[0068] The preparation method of modified nano silver-loaded zirconium phosphate is as follows:
[0069] 3 parts of nano silver-loaded zirconium phosphate were ultrasonically dispersed in 150 parts of deionized water, glacial acetic acid was added to adjust the system pH to 5, and then a mixed solution of 6 parts of γ-methacryloxypropyltrimethoxysilane and 120 parts of cyclohexane was added dropwise for 2 hours, and the mixture was heated to 60°C and reacted for 5 hours. After filtering, washing and drying, a modified nano silver-loaded zirconium phosphate was obtained;
[0070] The preparation method of the flame retardant is as follows:
[0071] Step (1): Under nitrogen protection, 15 parts of eugenol and 27 parts of epichlorohydrin are mixed evenly, 0.45 parts of benzyltriethylammonium chloride are added, the mixture is reacted at 100° C. for 6 hours, the temperature is lowered to 60° C., 25.5 parts of 30 wt % sodium hydroxide solution are added, the reaction is continued for 5 hours, and after filtering, washing, and rotary evaporation, eugenol glycidyl ether is obtained;
[0072] Step (2): Under nitrogen protection, 10 parts of DOPO and 15 parts of eugenol glycidyl ether were mixed evenly, the temperature was raised to 140° C., 0.5 parts of triphenylphosphine were added, the reaction was carried out for 7 hours, and the mixture was cooled to room temperature to obtain modified DOPO;
[0073] Step (3): Under nitrogen protection, 3 parts of cyanuric chloride are heated to 80° C., 9 parts of modified DOPO and 0.09 parts of calcium chloride are added, the reaction is carried out for 50 minutes, the temperature is raised to 100° C., the reaction is continued for 4 hours, and a dichloro compound is obtained by vacuum distillation;
[0074] Step (4): 5 parts of boric acid, 20 parts of diethanolamine and 30 parts of toluene are mixed uniformly, and refluxed at 125° C. until no water is produced in the system, and then distilled under reduced pressure, washed and dried to obtain diethanolamine borate;
[0075] Step (5): 10 parts of a dichloro compound, 5 parts of diethanolamine borate and 30 parts of DMF are mixed evenly, reacted at 130° C. for 2 h, DMF is evaporated off under reduced pressure, the temperature is raised to 200° C. and reacted for 4 h, and a flame retardant is obtained after washing and drying.
[0076] Comparative Example 1: A preparation process of a recycled polyester textile fabric, comprising the following processes:
[0077] Compared with Example 2, in Comparative Example 1, the modified nano silver-loaded zirconium phosphate in step S1 is replaced with nano silver-loaded zirconium phosphate of the same mass, and the other steps are the same as those in Example 2.
[0078] Comparative Example 2: A preparation process of a recycled polyester textile fabric, comprising the following processes:
[0079] Compared with Example 2, Comparative Example 2 does not include step S1, the composite is replaced with a flame retardant of the same mass, and the other steps are the same as those of Example 2.
[0080] Comparative Example 3: A preparation process of a recycled polyester textile fabric, comprising the following processes:
[0081] The preparation method of the flame retardant is as follows:
[0082] Step (1): Under nitrogen protection, 7 parts of eugenol and 12 parts of epichlorohydrin are uniformly mixed, 0.17 parts of benzyltriethylammonium chloride are added, the mixture is reacted at 95° C. for 5 hours, the temperature is lowered to 55° C., 11.5 parts of 30 wt % sodium hydroxide solution are added, the reaction is continued for 4 hours, and after filtering, washing, and rotary evaporation, eugenol glycidyl ether is obtained;
[0083] Step (2): Under nitrogen protection, 6 parts of DOPO and 7.2 parts of eugenol glycidyl ether were mixed evenly, the temperature was raised to 135° C., 0.24 parts of triphenylphosphine were added, the reaction was carried out for 6 hours, and the mixture was cooled to room temperature to obtain modified DOPO;
[0084] Step (3): Under nitrogen protection, heat 2.4 parts of cyanuric chloride to 75° C., add 12 parts of modified DOPO and 0.05 parts of calcium chloride, react for 40 minutes, heat to 95° C., continue to react for 3 hours, and obtain a dichloro compound by vacuum distillation;
[0085] Step (4): 2 parts of boric acid, 7.6 parts of diethanolamine and 10 parts of toluene are mixed uniformly, and refluxed at 120° C. until no water is produced in the system, and then distilled under reduced pressure, washed and dried to obtain diethanolamine borate;
[0086] Step (5): 6 parts of a dichloro compound, 2.7 parts of diethanolamine borate and 15 parts of DMF are mixed evenly, reacted at 125° C. for 1.5 hours, DMF is evaporated under reduced pressure, the temperature is raised to 195° C. for 3 hours, and a flame retardant is obtained after washing and drying;
[0087] Compared with Example 2, in step (3) of Comparative Example 3, the mass ratio of cyanuric chloride to modified DOPO is 1:5, and the other steps are the same as those of Example 2.
[0088] Comparative Example 4: The composite comprises the following components by mass: 7 parts of modified silver-loaded zirconium phosphate, 1 part of flame retardant, 0.2 parts of benzoyl peroxide, and 100 parts of xylene; other steps and processes are the same as those in Example 2.
[0089] Experiment: Take the modified polyester fibers obtained in Examples 1-3 and Comparative Examples 1-4, test their properties and record the test results: according to the national standard GB / T 2406-93, use an oxygen index meter to measure the limiting oxygen index (LOI value); measure the fiber strength on a fiber multifilament strength tester XL-2, with a clamping length of 500 mm and a test speed of 500 mm / min. Take 5 times for each sample, and the average value of the test results is obtained;
[0090] The antibacterial rate of the recycled polyester textile fabrics obtained in Examples 1-3 and Comparative Examples 1-4 was determined by the oscillation method according to the national standard GB / T 20944.3-2008. The sample size was 5 mm × 5 mm, and the strain used was Staphylococcus aureus (ATCC
[0091] 6538).
[0092] The test results are as follows:
[0093] LOI value (%) Fiber strength (cN / dtex) Antibacterial rate (%) Example 1 31.5 3.2 99.5 Example 2 32.4 3.0 99.8 Example 3 32.7 2.7 99.9 Comparative Example 1 30.2 2.1 98.4 Comparative Example 2 30.8 2.6 95.6 Comparative Example 3 31.2 2.8 99.3 Comparative Example 4 28.6 2.3 99.9
[0094] According to the data in the above table, we can clearly draw the following conclusions:
[0095] 1. Compared with Examples 1-3, the LOI value, fiber strength and antibacterial rate of the products obtained in Comparative Examples 1 and 2 are all reduced, indicating that the modified nano silver-loaded zirconium phosphate prepared by the present invention has better dispersibility and reactivity, improves the compatibility between inorganic nanoparticles and polyester fibers, thereby effectively improving the flame retardant properties, mechanical properties and antibacterial properties of the material; compared with the flame retardant, the composite prepared by the present invention also adds modified nano silver-loaded zirconium phosphate, which exerts a synergistic flame retardant and antibacterial effect, further improving the flame retardant properties, mechanical properties and antibacterial properties of the material.
[0096] 2. Compared with Examples 1-3, the LOI value and fiber strength of the product obtained in Comparative Example 3 are both reduced. It can be seen that adding excessive modified DOPO will reduce the mechanical properties. At the same time, the -Cl content in the remaining cyanuric chloride is reduced, thereby affecting the subsequent reaction and ultimately leading to a decrease in flame retardant properties.
[0097] 3. Compared with Examples 1-3, the LOI value and fiber strength of the product obtained in Comparative Example 4 are both reduced, indicating that the performance of the composite prepared by the present invention is affected by its component ratio. By selecting the component ratio within the range, the prepared material has excellent flame retardant effect.
[0098] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A process for preparing a recycled polyester textile fabric, characterized in that: The steps include: Step S1: Under nitrogen protection, ultrasonically disperse the modified nano silver-loaded zirconium phosphate in xylene, heat to 75-85° C., add benzoyl peroxide and flame retardant and mix evenly, react for 8-10 hours, cool to room temperature, centrifuge, wash and dry to obtain a composite; Step S2: mixing the dried recycled polyester chips and the composite, adding them into a twin-screw extruder, melt blending, extruding and granulating, and obtaining a modified polyester masterbatch; Step S3: mixing the modified polyester masterbatch and the recycled polyester chips, performing melt spinning, winding and stretching treatment to obtain modified polyester fibers; and plying, twisting and weaving the modified polyester fibers to obtain recycled polyester textile fabrics.
2. The process for preparing a regenerated polyester textile fabric according to claim 1, characterized in that: The compound comprises the following components by weight: 1-3 parts of modified nano silver-loaded zirconium phosphate, 2-10 parts of flame retardant, 0.1-0.3 parts of benzoyl peroxide, and 50-150 parts of xylene.
3. The process for preparing a regenerated polyester textile fabric according to claim 2, characterized in that: The preparation method of the modified nano silver-loaded zirconium phosphate is as follows: The nano silver-loaded zirconium phosphate was ultrasonically dispersed in deionized water, glacial acetic acid was added to adjust the pH value of the system to 4-5, and then a mixed solution of γ-methacryloxypropyltrimethoxysilane and cyclohexane was added dropwise for 1-2 hours, the temperature was raised to 50-60°C, the reaction was carried out for 3-5 hours, and the modified nano silver-loaded zirconium phosphate was obtained after filtering, washing and drying.
4. The process for preparing a regenerated polyester textile fabric according to claim 2, characterized in that: The preparation method of the flame retardant is as follows: Step (1): under nitrogen protection, eugenol and epichlorohydrin are mixed evenly, benzyltriethylammonium chloride is added, reacted at 90-100° C. for 4-6 hours, cooled to 50-60° C., sodium hydroxide solution is added, and the reaction is continued for 3-5 hours. After filtering, washing, and rotary evaporation, eugenol glycidyl ether is obtained; Step (2): Under nitrogen protection, DOPO and eugenol glycidyl ether are mixed evenly, the temperature is raised to 130-140° C., triphenylphosphine is added, the reaction is carried out for 5-7 hours, and the mixture is cooled to room temperature to obtain modified DOPO; Step (3): under nitrogen protection, heat cyanuric chloride to 70-80° C., add modified DOPO and calcium chloride, react for 30-50 min, raise the temperature to 90-100° C., continue to react for 2-4 h, filter, wash and dry to obtain a dichloro compound; Step (4): mixing boric acid, diethanolamine and toluene uniformly, and reacting under reflux at 115-125° C. until no more water is produced in the system, and distilling under reduced pressure, washing and drying to obtain diethanolamine borate; Step (5): uniformly mix the dichloro compound, diethanolamine borate and DMF, react at 120-130° C. for 1-2 h, evaporate the DMF under reduced pressure, raise the temperature to 190-200° C. for 2-4 h, and obtain a flame retardant after washing and drying.
5. The process for preparing a regenerated polyester textile fabric according to claim 4, characterized in that: In the step (3), the mass ratio of cyanuric chloride, modified DOPO and calcium chloride is 1:(2-3):(0.01-0.03).
6. The process for preparing a regenerated polyester textile fabric according to claim 1, characterized in that: In the step S2, the mass ratio of the recycled polyester chips to the composite is 1:(0.05-0.20).
7. The process for preparing a regenerated polyester textile fabric according to claim 1, characterized in that: In step S3, the mass ratio of the modified polyester masterbatch to the recycled polyester chips is 1:(10-12).
8. The process for preparing a regenerated polyester textile fabric according to claim 1, characterized in that: The temperature of the melt blending is 230-270°C.
9. The process for preparing a regenerated polyester textile fabric according to claim 1, characterized in that: The temperature of the melt spinning is 270-290° C., and the winding speed is 600-900 m / min.
10. A regenerated polyester textile fabric obtained according to the preparation process according to any one of claims 1 to 9.
Citation Information
Patent Citations
Production method of recycled phosphorus flame retardant polyester staple fibre
CN102747455A
Cyanuric-chloride-based benzothiazole ESIPT compounds, and preparation method and purpose thereof
CN102993194A
Antibacterial polyester fiber combination yarn and preparation method thereof
CN111364139A
Eugenol-based silicon-containing flame retardant as well as preparation method and application thereof
CN115850340A
Method for preparing multifunctional acoustic panel by regenerating waste polyester fabric
CN117903578A